(untitled) (ENTHYMEMA, 2016)
Lindsay Holmgren’s “Empathic Communications and Narrative Competence in Contemporary Medical Education” reviews the teaching of narrative competency in medical education, arguing that these practices must engage postclassical approaches to narrative studies while attending to the concept of empathy as it is deployed in various disciplines, including narratology, cognitive science, and psychology. With an emphasis on the formation of professional identity in medical practice, Holmgren explores the relationship between professional identity in a multi-ethnic, gender-neutral, demographically and culturally diverse medical education context, and the complex arena of narrative empathy. Hinging her argument on the reciprocal nature of identity that emerges at the intersections of various versions of the self and others, Holmgren’s article aligns the empathy developed by reading fiction with that which develops in the clinical encounter. Finally, the article understands these various, evolving subject positions rhetorically, arguing that the comportments of medical educators in the humanities should be such that their students will want to emulate them.